2009
DOI: 10.1177/089686080902900503
|View full text |Cite
|
Sign up to set email alerts
|

Peritoneal Dialysis in Brazil: Twenty-Five Years of Experience in a Single Center

Abstract: Objectives To evaluate patient and technique survival and to provide an analysis of peritoneal dialysis (PD)-related peritonitis in 25 years of experience in a single center. Study Design Retrospective study of incident patients on PD from July 1980 to July 2005. Setting Single, university based, Brazilian dialysis program. Patients 680 patients were analyzed in our study from July 1980 to July 2005, with a cumulative experience of 15303 patient-months. All patients over 15 years of age entering the dialysis p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
0
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 23 publications
4
15
0
6
Order By: Relevance
“…[ 23 ] and Moraes et al . [ 31 ] have reported culture negative peritonitis similar to our study (33.7% and 26% respectively).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…[ 23 ] and Moraes et al . [ 31 ] have reported culture negative peritonitis similar to our study (33.7% and 26% respectively).…”
Section: Discussionsupporting
confidence: 90%
“…Fernandes et al ., in a large national multicenter study (Brazilian Peritoneal Dialysis Multicenter Study),[ 30 ] have reported an overall peritonitis rate of one episode every 30 months with a mean follow-up of 13.6 months (most frequently due to S. aureus ), while Moraes et al ., in a single center study[ 31 ] have reported one episode every 14.63 months when describing 25-year cumulative data in Brazil.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The success of a PD service programme depends on many factors that are interlinked and inseparable from one another (Moraes et al 2009;Nayak et al 2012). Nayak (2007) has defined a dozen key points for a successful programme including patient selection, personnel management, product selection, PD prescription and pharmacotherapy, protein calorie intake, patient on line support, peritonitis, exit-site infection and other complication, preservation or renal function, physiotherapy and rehabilitation, purse management of patients, post-graduation fellowship and academic activities.…”
Section: Quality Improvement In a Pd Unitmentioning
confidence: 99%
“…It contributes to ∼20% of PD technique failures [1], results in an overall mortality rate of 2-6% [2,3] and is a major barrier to the selection of PD as a renal replacement therapy modality by patients with end-stage kidney disease (ESKD). Single-centre studies in Korea [4], Brazil [5], Portugal [6] and Taiwan [7] have reported decreasing peritonitis rates over time. This pleasing trend has been ascribed primarily to improvements in PD connectology [8] and exit site care [9] as these innovations have resulted in decreased risks of touch contamination, intra-luminal entry of organisms or exit site colonization or infection leading to reduced peri-luminal entry of organisms.…”
Section: Introductionmentioning
confidence: 99%